2010
DOI: 10.1128/aem.00653-10
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Microorganisms in the Disease-Like Syndrome Affecting the Sponge Ianthella basta

Abstract: A disease-like syndrome is currently affecting a large percentage of the Ianthella basta populations from the Great Barrier Reef and central Torres Strait. Symptoms of the syndrome include discolored, necrotic spots leading to tissue degradation, exposure of the skeletal fibers, and disruption of the choanocyte chambers. To ascertain the role of microbes in the disease process, a comprehensive comparison of bacteria, viruses, fungi, and other eukaryotes was performed in healthy and diseased sponges using multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 39 publications
7
76
0
Order By: Relevance
“…Bourne et al 2008. Indeed, there has been a recent conceptual change, moving away from focusing on microbial pathogens as disease-causing agents to recognizing the relevance of intrinsic microbial com munity shifts prior to or during disease progression (Webster et al 2008, Luter et al 2010, Angermeier et al 2011. Even though there is experimental evidence for the presence of bacteria implicated in sponge and coral disease in SWP-afflicted Amphi medon compressa, tissue transplantation trials failed to provoke a SWP phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bourne et al 2008. Indeed, there has been a recent conceptual change, moving away from focusing on microbial pathogens as disease-causing agents to recognizing the relevance of intrinsic microbial com munity shifts prior to or during disease progression (Webster et al 2008, Luter et al 2010, Angermeier et al 2011. Even though there is experimental evidence for the presence of bacteria implicated in sponge and coral disease in SWP-afflicted Amphi medon compressa, tissue transplantation trials failed to provoke a SWP phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Sponge diseases have thus far been reported from many geographic regions, including the Great Barrier Reef, the Indo-Pacific, the Mediterranean and the Caribbean (Harvell et al 1999). Sponge diseases that have already been reported include Aplysina red band syndrome (ARBS) (Olson et al 2006), Aplysina black patch syndrome (Webster et al 2008), sponge orange band (SOB) disease of Xestospongia muta (Cowart et al 2006, López-Legentil et al 2010, Angermeier et al 2011), brown lesion necrosis or disease-like syndrome of Ianthella basta (Cervino et al 2006, Luter et al 2010, spongin-boring necrosis of Rhopaloides odorabile (Webster et al 2002) and pustule disease of Ircinia fasciculata and I. variabilis (Maldonado et al 2010). Outbreaks of various sponge diseases have indeed proven to be fatal on several occasions in different localities (Gaino et al 1992, Vacelet et al 1994, Maldonado et al 2010, Cebrian et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, individuals of Ianthella basta are found in a variety of colour morphotypes (yellow, brown, green, blue or purple), with the purple and yellow dominating on the inshore Great Barrier Reef. Recent investigations of the microbial communities within I. basta have found the community to be dominated by members of the Alpha and Gammaproteobacteria, although the more exhaustive 454 tag pyrosequencing study conducted by Webster and colleagues identified additional representatives considered to be part of the rare biosphere (Luter et al, 2010;Webster et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have shown that uncultured Oscillatoriales are often associated with marine sponge and coral diseases [21,26,40,76], these cyanobacteria being high-ly represented in diseased L. baicalensis. Some detailed investigations revealed several putative pathogens within this order.…”
Section: Discussionmentioning
confidence: 99%
“…Acidobacteria, Actinobacteria, Bacteroidetes, Chloroflexi, Cyanobacteria, Proteobacteria (Alphaproteobacteria, Betaproteobacteria, Gammaproteobacteria, Deltaproteobacteria), Verrucomicrobia, and Nitrospira phyla are the most common both in marine [4,10] and freshwater sponges [11][12][13][14]. Sponge disease outbreaks or mass mortality events have been reported for more than a century, with more than 20 events studied, sometimes affecting several species and large areas [4,[15][16][17][18][19][20][21][22][23][24][25][26][27][28]. However, reports and investigations on the conditions of freshwater sponge disease outbreaks are rare.…”
Section: Introductionmentioning
confidence: 99%